Monitoring adipose tissue blood flow in man: a comparison between the (133)xenon washout method and microdialysis. - Karpe, F; Fielding, B; Ilic, V; Ilic, V; Humphreys, S; Humphreys, S; Frayn, K; Frayn, K (2002)
INTRODUCTION: Adipose tissue blood flow (ATBF) increases after meal intake and a failure to regulate ATBF in the postprandial period seems to be a feature of insulin resistance and obesity. ATBF can be measured quantitatively by the (133)Xe washout technique, but the microdialysis ethanol escape method has also been employed to detect relative changes in ATBF. METHODS: We compared (133)Xe washout and the recovery of exogenous ethanol and endogenous urea by microdialysis in abdominal subcutaneous adipose tissue, after physiological stimulation of ATBF by ingestion of oral glucose (75 g) in eight healthy people (age 23-52 y, body mass index (BMI) 19.4-29.6 kg/m(2)). RESULTS: The ATBF response was heterogeneous. In subjects responding vigorously to the stimulus as measured by (133)Xe washout, the microdialysis ethanol escape was increased (indicating an increase in ATBF). An increased recovery of urea was observed, also indicating an increase in ATBF. The recovery of both small molecules was delayed compared with increased blood flow and failed to return to baseline in response to a rapid decline in ATBF. CONCLUSION: We conclude that the (133)Xe washout technique is more responsive to physiological change in ATBF than ethanol escape or urea recovery by microdialysis.